75.1k views
5 votes
Z+(z-6)-2=-10
How donI solve this?

2 Answers

7 votes

Answer:

z= -1

Explanation:

Simplifying

z + (z + -6) + -2 = -10

Reorder the terms:

z + (-6 + z) + -2 = -10

Remove parenthesis around (-6 + z)

z + -6 + z + -2 = -10

Reorder the terms:

-6 + -2 + z + z = -10

Combine like terms: -6 + -2 = -8

-8 + z + z = -10

Combine like terms: z + z = 2z

-8 + 2z = -10

Solving

-8 + 2z = -10

Solving for variable 'z'.

Move all terms containing z to the left, all other terms to the right.

Add '8' to each side of the equation.

-8 + 8 + 2z = -10 + 8

Combine like terms: -8 + 8 = 0

0 + 2z = -10 + 8

2z = -10 + 8

Combine like terms: -10 + 8 = -2

2z = -2

Divide each side by '2'.

z = -1

Simplifying

z = -1

User Siki
by
4.7k points
4 votes

Answer:

z = -1

Explanation:

Simplifying

z + (z + -6) + -2 = -10

Reorder the terms:

z + (-6 + z) + -2 = -10

Remove parenthesis around (-6 + z)

z + -6 + z + -2 = -10

Reorder the terms:

-6 + -2 + z + z = -10

Combine like terms: -6 + -2 = -8

-8 + z + z = -10

Combine like terms: z + z = 2z

-8 + 2z = -10

Solving

-8 + 2z = -10

Solving for variable 'z'.

Move all terms containing z to the left, all other terms to the right.

Add '8' to each side of the equation.

-8 + 8 + 2z = -10 + 8

Combine like terms: -8 + 8 = 0

0 + 2z = -10 + 8

2z = -10 + 8

Combine like terms: -10 + 8 = -2

2z = -2

Divide each side by '2'.

z = -1

Simplifying

z = -1

User Justin French
by
5.3k points